Analisis Pelaksanaan Pekerjaan Konstruksi Preservasi Jalan Long Segment Berbasis Manual Program Evaluation And Review Technique (M-Pert) Dan Value Engineering (Ve) - al-imam, ahmad fikry; Widyaningsih, Nunung; Suroso, Agus (Universitas Mercu Buana, 2024)
The provision in the 2014 National Medium-Term Development Plan (RPJMN) for the distribution of packages of national road preservation and maintenance activities with the Long Segment contract scheme was chosen by the Directorate General of Highways to improve connectivity between regions as set out in the infrastructure development strategy in Indonesia. The problem of delays in project implementation and work cost efficiency on road projects based on Long Segment contracts. The expected goal in this research was time and cost efficiency using the Manual Program Evaluation and Review Technique (M-PERT) and Value Engineering (VE) method. The analysis resulted in influencing factors, namely the process of activity stages (RII = 0.911), Planning (RII = 0.936), Implementation (RII = 0.919), Supporting (RII = 0.882) Structural Planning (RII = 0.952) Supervision (RII = 0.871) External conditions (RII = 0.769) and road preservation works (RII = .864). The case study using M-PERT method obtained a time optimization value of 1.21% with an accuracy of 98.79% of the completion time at the job site.